Pengaturan Persetujuan Bangunan Gedung Di Kota Payakumbuh - Haswin, Olvi Sri Hilda; Fendri, Azmi; Rosari, Anton (Faculty of Law, Andalas University, 2024)
Building Approval is a change in nomenclature from Building Permit. It has been the case since Law Number 11 of 2020 concerning Job Creation took effect. When organizing a building, whether constructing a new one or making changes to an existing one, ownership of the Building Approval (PBG) is required. The authority for issuing PBGs has shifted from the One-Stop Investment and Integrated Service (DPMPTSP) through the OSS Site (Online Single Submission) to the Public Works and Public Housing Office (PUPR) through SIMBG (Building Management Information System) managed by the Ministry of PUPR. In this change, the problems that will be studied are: 1. How is the building approval regulation in Payakumbuh City? 2. What are the benefits of implementing building approvals in Payakumbuh City? The author uses empirical juridical research methods and a descriptive-analytical approach to answer these questions. The primary data in this research was obtained through interviews. Secondary data is obtained by conducting document studies. Data analysis is conducted qualitatively. The research yielded the following results: 1. During the transition period from IMB to PBG, there is no local regulation related to PBG in Payakumbuh City. However, the PUPR and DPMPTS offices continue to exercise their authority based on the law and its implementation regulations. Several impacts exist, including reduced local revenue, challenges in employee capabilities and qualifications, issues with technology implementation, a lack of community understanding regarding the procedures and requirements for PBG applications through the SIMBG system, and overlapping regulations related to Building Approval Retribution. 2. The research also identified several benefits of having a PBG, including enhanced Legality, Security, Order, Commercial Advantages, Ease of Licensing, A Healthier Environment, and Increased Local Revenue.